Desain dan Perancangan Sistem Bimbingan Skripsi dengan Model Total Architecture System (TAS) Studi Kasus pada Jurusan Akuntansi Politeknik Negeri Semarang - Afiat Sadida; Sarana Sarana; Agus Suwondo; Prima Ayundyayasti (Lembaga Yasin AlSys, 2025)
The absence of an integrated thesis supervision system in the Accounting Department of Politeknik Negeri Semarang presents a significant issue, given the importance of monitoring the supervision process to support timely student graduation. This study aims to design an effective thesis supervision management system that facilitates the monitoring and management of the supervision process. The research employs a system development approach based on Unified Modelling Language (UML) within the Total Architecture Synthesis (TAS) framework. The database utilized is MySQL, supported by the XAMPP web server. System requirements were gathered through observations and interviews with academic supervisors and department administrators. The outcome of the study is a system design comprising database architecture, user interface prototypes, and a structured supervision workflow. The system is designed to assist lecturers and students in tracking supervision progress, minimizing administrative barriers, and supporting the achievement of higher education Key Performance Indicators (KPIs). Practically, this study delivers a prototype system that can be implemented in the Accounting Department or adapted by other programs with similar needs. Theoretically, it contributes to the development of information technology-based supervision management models in vocational education settings.